KOMUNIKASI INTERPERSONAL PENERIMA MANFAT DENGAN PEKERJA SOSIAL DI PANTI SOSIAL BINA REMAJA (PSBR) RUMBAI KOTA PEKANBARU - Reva Masriana; Desti Irja; Said Suhil Achmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to find out the good interpersonal communication of beneficiaries with social workers at the Rumbai City Youth Development Board (PSBR), Pekanbaru. Based on observations on the Bina Remaja Social Institution, the following phenomena are encountered: 1. There are several recipients who are closed in doing interpersonal communication in social care institutions. 2. The existence of several beneficiaries do not care about the opinions of others in carrying out interpersonal communication. 3. The existence of several beneficiaries who provide a positive boost in the process of interpersonal communication 4. There is a positive assessment given by beneficiaries in the communication process so that beneficiaries feel comfortable in carrying out interpersonal communication. 5. There are several beneficiaries who carry out the communication process by distinguishing the other person in the social care institution. This type of research is descriptive with a quantitative approach. The population in this study were beneficiaries who were in the Teenage Community Development Center (PSBR) Rumbai, Pekanbaru. The sampling technique in this study used a probability sampling technique type of simple random sampling using the Slovin formula. The instrument in this study was a questionnaire instrument variable in the form of a questionnaire using a Likert scale consisting of five answer choices From the findings of this study, it can be seen that beneficiary interpersonal communication in the environment of Adolescent Community Development (PSBR) Tassel in Pekanbaru is high, this can seen from the Mean (3.67) and Standard Deviation (0.78) from the average research indicator. Key Words: Interpersonal Communication, Beneficiaries, PSBR